Evaluation of the use of corrosion inhibitors in the acid pickling of a galvanic plant - Sánchez Vargas, Héctor Eduardo (2021)
The protection by coatings constitutes the most used method of anticorrosive combat, given its effectiveness, economy, universality and ease of application. However, the use of these coatings at an industrial level entails a high consumption of energy and chemical products, as well as a marked environmental impact. One of the ways to minimize the negative effects in this type of process is the use of corrosion inhibitors. This work had the objective of showing the results of an investigation in which an evaluation was carried out for the introduction of corrosion inhibitors in the acid pickling operation of a galvanic workshop. As research methods and techniques, documentary review, observation, experimental studies were used, in addition, mathematical modeling techniques and process optimization were applied. The main results were: the demonstration of the feasibility of the use of formaldehyde and urotropin for the conditions of the workshop; The optimum concentration of the inhibitor in the acid pickling solution was determined; It was concluded that the combinations of both inhibitors with sulfuric acid turn out to be the best, with the lowest pickling cost for optimal conditions compared to the rest of the acid-inhibitor combinations.